A marine chitinase from Bacillus aryabhattai with antifungal activity and broad specificity toward crystalline chitin degradation. Issue 10 (1st November 2022) - Subramani, Arun Kumar; Raval, Ritu; Sundareshan, Subramaniam; Sivasengh, Rashmi; Raval, Keyur
Abstract: Chitinases convert chitin into chitin oligomers and are also known antifungal agents. Chitin oligomers have numerous industrial applications. However, chitin's crystalline nature requires pretreatment before breakdown into oligomers. In the study, a novel marine bacterium Bacillus aryabhattai is isolated from the Arabian Sea. Bacterial growth in different crystalline chitin substrates like chitin powder, chitin flakes, and colloidal chitin confirmed the chitinase presence in bacterium could act upon insoluble crystalline chitin with the fractional release of oligomers. The domain architecture analysis of the chitinase confirmed the presence of two N-terminal LysM domains which help enzyme action on crystalline chitin. Statistical optimization of media and Process parameters revealed glycerol, yeast extract, magnesium chloride, and manganese sulfate as significant media components along with colloidal chitin. The optimum process parameters such as pH 7, temperature 40 °C, inoculum size 12.5% (v/v), and inoculum age 20 hours enhanced the specific enzyme activity to ±146.2 U/mL, ±114.9 U/mL and ±175.4 U/mL against chitin powder, chitin flakes and colloidal chitin respectively, which is five to six times higher than basal level activity. The antifungal activity of chitinase against plant pathogenic fungi like Candida albicans and Fusarium oxysporum revealed a zone of inhibition with 14 mm diameter.